Bridges to sustainable health systems: public-private interaction for market access. Issue 12 (13th April 2020) - Guercini, Simone; Milanesi, Matilde; Runfola, Andrea
Abstract : Purpose: This paper aims to investigate the market access (MA) of ethical drugs, the underlying public-private interaction (PPI) between pharmaceutical companies and public actors, and the implications for the sustainability of the health system. Design/methodology/approach: A qualitative interpretivist approach was selected. Interviews were carried out as the primary method of data collection: 27 interviews were conducted with 13 key informants from the pharmaceutical industry. Findings: The perspective of MA evolves from formal negotiation with the public actor at various levels to PPI, which should include aspects of interactions with other actors in the network. Conceptualization in these terms is fundamental because it allows an understanding of the implications in terms of the sustainability of the health system. Originality/value: The paper discusses MA by highlighting the shift from a "market access as formal negotiation" perspective to a "public-private interaction for market access" perspective, in which the focus is on the content of the interaction and the representation of the network of relevant actors for MA. It contributes to the debate on the sustainability of health systems by suggesting the adoption of a medium-to-long-term approach to economic and social sustainability based on PPI; it adopts an industrial marketing approach and contributes to the recent debate on PPI.